Inter-firm cooperation in entrepreneurial networks: Case Likiliike - Ruokamo, Taija (My University, 2019)
Recently, the research field in entrepreneurship has experienced an increase in studies concentrating on networks. Networks are crucial for entrepreneurs, since they provide access to important tangible and intangible resources. Entrepreneurs’ capability to establish and maintain cooperative relationships is critical for entrepreneurial success. The existing literature on how, when, and why ties change and become cooperative is scarce, and more evidence is needed on network capabilities in the context of micro- and small-sized enterprises. This re-search studies development of inter-firm cooperation in entrepreneurial networks and aims to fulfill the gap in the existing literature. This research examines the barriers, risks, and opportunities for developing inter-firm cooperation in entrepreneurial networks and suggests what network capabilities are needed to enable development of inter-firm cooperation. The research was conducted as a single case study using a qualitative method. The case of the study is a large and multisectoral entrepreneurship society operating in the Finnish Lapland in the city of Rovaniemi. The empirical data was collected in seven semi-structured interviews and from other secondary sources. The findings indicate that development of inter-firm cooperation in a large and heterogeneous network is unlikely. There should be enough similarities between actors so that development of cooperation is possible, but also differences so that heterogeneous resources exist in the network. Furthermore, inter-firm cooperation does not develop on its own; network manager should provide conditions in order to enable development of inter-firm cooperation. Main barriers for development of cooperation were lack of interest, scarce resources, and skepticism towards cooperation. However, inter-firm cooperation can lead to multiple opportunities, such as joint problem-solving arrangements, complex information exchange, and competitive advantage. Most important network capabilities needed to develop inter-firm cooperation for network members were cooperation-orientation, social competence, capability to initiate relationships, and information exchange capability. Network members also need visioning and coordination capability, but these capabilities are especially important for network manager. Future research possibilities could be conducting a longitudinal study in order to provide insight on how entrepreneurial networks develop over time. Also, conducting more research on information exchange capability could be useful, since the existing literature on the capability is limited.
Keywords: entrepreneurial network; cooperation; network capability; social capital; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|